Examining the relation between emotional experiences and emotional expressions in competitive tennis matches - Fritsch, Julian; Fiedler, Janis; Hatzigeorgiadis, Antonis; Jekauc, Darko (Frontiers in Psychology, 2024)
Emotions consist of different components such as the emotional experience, physiological reactions, action tendencies, or emotional expressions. Assessing the relation of these components may help to better understand the role of emotions in sport competitions. Based on the component process model of emotions, the goal of the present study was to assess the relation between emotional experiences and emotional expressions. To that end, 20 tennis players (7 female) with an average age of 23.10 (SD = 4.88) were taped during competitive tennis matches. Thereafter, in individual meetings, after having watched themselves on the footage at pre-selected points, the players had to indicate whether, immediately after the end of a rally, they had a positive or a negative emotional experience and, in case they had one, rate its intensity. Moreover, based on their observable behaviour, the players were also asked to state whether they could recognize a positive or a negative emotional expression and, in case they recognized one, rate its intensity. The occurrence of emotional expressions was additionally rated by two external coders. Using multilevel models, separate analyses were conducted for positive emotions after won points and negative emotions after lost points. For both positive and negative emotions, the results indicated a positive correlation between emotional experiences and emotional expressions. Moreover, the intensity of emotional experiences could predict the occurrence of an emotional expression rated by both the players or external coders. These insights into the relation between emotional experiences and emotional expressions may help players to more effectively regulate their emotions.